Model Studi Kelayakan Bisnis Berbasis Maqāṣid al-Syariah dalam Perspektif Ekonomi Islam - Nur Aprida (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2026)
The growth of entrepreneurship and the halal industry in Muslim countries has shown significant progress, but business practices are still largely oriented towards profitability without considering the ethical dimensions and social welfare that are the main principles of Islamic economics. Conventional business feasibility studies generally assess market, technical, managerial, legal, social, and financial aspects, but have not fully integrated the values ​​of maqāṣid al-Shari'ah as a normative foundation in economic activity. This study aims to formulate a conceptual framework for business feasibility studies based on maqāṣid al-Shari'ah and identify maqāṣid indicators in each main aspect of business feasibility studies. The study uses a qualitative approach with a literature study method through analysis of various classical and contemporary literature on maqāṣid al-Shari'ah, Islamic economics, and business feasibility studies. Data were analyzed using content analysis techniques with a descriptive-analytical approach. The results of the study indicate that the integration of maqāṣid al-shariah in business feasibility studies produces a more comprehensive evaluation model by mapping market, technical, managerial, legal, socio-environmental, and financial aspects against the five main objectives of maqāṣid, namely the protection of religion, life, intellect, descendants, and property. This model also allows for the classification of the level of business benefits based on the categories of daruriyyāt, hajiyyāt, and tahsiniyyāt. The implications of the study indicate that this approach can be an alternative framework in assessing business feasibility that considers not only profitability, but also social sustainability, ethics, and community benefits more holistically.